Analysis of Application of Sharia Principles in Improving the Quality of Hospitality and Lodging Consumer Services ( Reddoorz Syari'ah U Case Study, Medan issue ) - Haidir Hasibuan (Budapest International Research and Critics University, 2022)
Along with the development of the Islamic economy in Indonesia, Currently, many institutions apply sharia principles in carrying out their activities business, one of which is the Syariah Hotel, which is a hotel as usual, which operations and services have adapted to the principles of sharia or Islamic teachings. This research raises the formulation of the problem, namely: how to apply sharia principles at the Medan Sharia Transit Hotel. And this study aims to find out how the application of sharia principles at the Hotel Transit Syariah Medan. This study uses descriptive research with data analysis qualitative, problem-solving procedures investigated by describing, describing the state of the object at present based on the facts looks and as it is with the technique of observation, interviews, and documentation. The results of this study are that the Application of Sharia Principles has been implemented, including the rules and policies of the hotel as a whole. but there are still drawbacks in terms of cleanliness and facilities that need to be improved. And this kind of hotel model is in great demand by the public, especially Muslims because of aspects of comfort, safety, and services provided.